PEMBELAJARAN MODIFIED FREE INQUIRY BERBANTU E-LKPD UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA - Amanah, Sifa Pajar; Widiantie, Rahma; Handayani, Handayani (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
One of the current issues in education is the low level of students"™ science process skills, which should be a key component in developing 21st-century competencies. This issue is caused by several factors, including limitations in implementing inquiry-based learning models and the minimal use of technology-based learning materials such as E-LKPD. This study aims to analyze the improvement of students"™ science process skills through the implementation of the Modified Free Inquiry learning model assisted by E-LKPD on the excretory system topic at SMA Negeri 2 Kuningan. The research method used was a quasi-experimental design with a non-equivalent control group design. The study subjects consisted of two classes: the experimental class, which received treatment using the Modified Free Inquiry learning model assisted by E-LKPD, and the control class, which used the Discovery Learning model assisted by E-LKPD. Instruments used included essay tests (pretest and posttest), student response questionnaires, observation sheets of science process skills performance, and learning implementation observation sheets. The results showed an improvement in science process skills in both the experimental and control classes. The experimental class achieved a higher N-Gain score in the moderate category, and the Mann-Whitney hypothesis test showed that Zcount > Ztable, indicating that H0 is rejected and H1 is accepted. In addition, the science process skills performance observation sheet showed an average score of 73 in the good category, students gave positive responses to the learning process with an average questionnaire score in the very good category, and learning implementation reached 97% in the very good category. Therefore, the Modified Free Inquiry learning model assisted by E-LKPD is effective in improving students"™ science process skills and is feasible to be implemented in biology learning.